Dysfunctional levels of corona virus-related anxiety in medicine students - Costa, Ricardo Alves (2022)
Objective: The aim of this research is to verify dysfunctional levels of anxiety in medical students during the COVID-19 pandemic. Methods: 656 medical students in Brazil were evaluated through a cross-sectional, exploratory and quantitative study. Data were collected in May and June 2020, through two self-administered questionnaires. The first was an instrument developed by the authors themselves to assess the sociodemographic profile of the studied sample. To assess anxiety symptoms, the Coronavirus Anxiety Scale - an instrument to assess dysfunctional levels of anxiety related to the COVID-19 pandemic - was used. Results: The prevalence of individuals with dysfunctional levels of anxiety related to the COVID-19 pandemic was 7.6% (n = 50). Risk factors for the manifestation of anxiety symptoms related to the new coronavirus are: having the course interrupted during the pandemic, experiencing the feeling of not learning anything, having a previous diagnosis of mental disorder, living with someone who works outside the home, being together the affective partner, friends or family members, and being unable to maintain healthy habits during the pandemic, having intra-household contact with someone infected, being afraid of the disease or having manifested symptoms. Conclusion: This study showed a significant number of medical students with dysfunctional levels of anxiety and given the results obtained, it was seen that there was a need for a more direct approach to mental health in universities and in the media.